Contrasting Features of Monsoon Precipitation Around the Meghalaya Plateau Under Westerly and Easterly Regimes. Issue 18 (21st September 2017) - Fujinami, Hatsuki; Sato, Tomonori; Kanamori, Hironari; Murata, Fumie
Abstract: Precipitation features around the Meghalaya Plateau, northeast India, during summer are investigated using a 17 year (1998–2014) high‐spatial‐resolution Tropical Rainfall Measuring Mission precipitation radar data set. Precipitation around the plateau fell into two distinct regimes based on the low‐level wind direction that fluctuates on intraseasonal time scales over Bangladesh, windward of the plateau: a westerly regime (WR) and an easterly regime (ER). Under the WR, strong low‐level onshore southwesterlies across Bangladesh encounter the plateau, and localized strong low‐level southerlies running parallel to the Arakan Mountains (i.e., the barrier jet) also blow toward the plateau, concentrating convective unstable air onto its southern slopes. The low‐level wind fields and large‐scale upper level divergent fields promote frequent and intense orographic rainfall along the southern slopes due to forced uplift, generating high precipitation. In contrast, under the ER, strong southeasterlies that blow along the Gangetic Plain without encountering the plateau and subsidence inhibit upward motion around the plateau, resulting in low precipitation. Diurnal variations in precipitation significantly affect the daily precipitation around the plateau under both regimes. High rainfall frequency persists over the southern slopes between 2100 and 1200 LT of the next day under the WR, whereas modest rainfall frequency occurs between 0000 and 0600 LT under the ER, with a daytime minimum and nocturnal maximum in both regimes. The atmospheric boundary layer processes over Bangladesh regulate the wind speed and vertical structure of the low‐level wind toward the plateau, with deceleration during daytime and acceleration at night (i.e., nocturnal jet) that result in the nocturnal rainfall maximum. Key Points: Precipitation properties around the Meghalaya Plateau in summer from 17 years of TRMM Precipitation Radar (PR) data Multiscale relationship between intraseasonal oscillation and diurnal variation Effects of land‐atmosphere interaction and regional‐scale orography on precipitation Plain Language Summary: The Meghalaya Plateau of northeast India is one of the wettest places in the world. Extreme rainfall often causes flooding across the flat lowlands of Bangladesh to the south of the plateau. This study reveals the features contributing to this heavy rainfall and the mechanisms responsible using a 17 year (1998–2014) high‐spatial‐resolution spaceborne precipitation radar (TRMM‐PR) data set and state‐of‐the‐art atmospheric circulation data (ERA‐Interim). Precipitation around the plateau is highly sensitive to whether strong low‐level southerly monsoon winds from the ocean have westerly or easterly components (westerly and easterly regimes, respectively) over Bangladesh, windward of the plateau. Under the westerly regime, strong low‐level southwesterlies blow over Bangladesh directly toward the plateau and localized strong low‐level southerlies running parallel to the Arakan Mountains also blow toward the plateau. These winds concentrate moist air onto the southern slopes of the plateau, and rainfall occurs as the air is forced upward. The large rainfall amounts are caused by frequent heavy rain. In contrast, under the easterly regime, strong southeasterlies blow along the Gangetic Plain through northwestern Bangladesh and avoid the plateau, resulting in less frequent and lighter rain around the plateau.